Deliberative Republicanisms to debate. A political philosophical analysis of “La forma del derecho” from Fernando Atria - Emanuel Olivares, Nicolás (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
In this work we propose three specific objectives. Firstly, to reconstruct the main normative assumptions of the comprehensive republican conception of the concept of deliberative democracy assumed by F. Atria in his work La forma del derecho. Secondly, to present a diverse deliberative republican conception, defined by four characters: political, reflexive, civic and epistemic. Thirdly, to point out in what sense this second conception would respond adequately to the challenge of justifying a democratic model that overcomes the pressing and current but apparent skeptic-objectivist paradox in matters of political truth.
Keywords: Deliberative democracy, comprehensive republican conception, human dignity, mutual recognition, political republican conception, non domination, citizen reciprocity.